(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
Today, the most important issue of effective employment of young people in labor activity is the issue of national and state importance. Because today, the composition of labor collectives in various sectors of our economy, the young men and women joining the ranks of entrepreneurs, will determine the development of Uzbekistan in the next 30-40 years.